Towards a mental health democracy - Stelios Stylianidis; Panagiotis Chondros; Kyriakos Souliotis (Dialogues in Clinical Neuroscience & Mental Health, 2018)
Introduction Despite advances in research and medical technology, between 76% and 85% of people with serious mental disorders had received no treatment in the previous year according to the world mental-health survey conducted by the WHO in 2011 (1). Still, nowhere in the world does mental health enjoy parity with physical health in national policies and budgets or in medical education and practice (2,3,4). Although WHO has stressed the importance of social determinants in health and mental health, public policies continue to neglect how poverty affects mental health, creates violence, social exclusion and breakdown of communities. As the Special Rapporteur to the UN on the right of everyone to enjoy the highest attainable standard of physical and mental health points out precisely “the crisis in mental health should be managed not as a crisis of individual conditions, but as a crisis of social obstacles, which hinders individual rights. Mental health policies should address the “power imbalance” rather than “chemical imbalance” (3:19). These obstacles are: • Dominance of the biomedical model • Power asymmetries • Biased use of evidence in mental health